Case Report: Late Complication of a Dry Socket Treatment - Ramón Manuel Alemán Navas; María Guadalupe Martínez Mendoza (International Journal of Dentistry)
Dry socket is often treated in dentistry with intra-alveolar dressings; the use of them remains controversial and has been related to some side effects such as neuritis, foreign body reactions, and myospherulosis. We present a case of an intra-alveolar dressing (zinc-oxide eugenol paste) that mimicked a trigeminal neuralgia for 3 years and caused a right maxillary chronic osteomyelitis and foreign body reaction in a zone corresponding to the alveolus of the maxillary first molar. This long-term complication was successfully managed by complete removal of the foreign body and curettage of the affected area.